Minority report researching indigenous people at the UP College of Mass Communication - Dy, Richard Jacob N. 1991-; Portus, Lourdes M. (2012)
"This thesis examines the researches on indigenous people (IP) conducted in the College of Mass Communication from the year 2000 to 2010. By analyzing the IP research in the college, we aimed to a) identify the indigenous groups studied, b) know how the researchers chose the IP group for their theses, c) describe the written research output, d) know the traditions, practices, and protocols followed in IP research, and e) enumerate issues and challenges encountered in the conduct of research. Content and Textual Analysis were conducted on the theses and dissertations submitted to the five departments of the college. A focus interview was also conducted with one of the IP researchers whose study we analyzed.This study shows the ongoing oppression by Philippine IP groups as reflected in the theses submitted to UP CMC. This domination is felt in the areas of IP media representation, ancestral domain claim and economic relations. The researcher-IP groups relationship was also shown to benefit the researcher more than the IP community. With the findings presented in this study, we hope to assist in the research endeavors of future IP researchers in UP CMC as well as contribute towards the overall improvement of IP research in the college."
Vita.
Undergraduate thesis (A.B. Communication Research)--University of the Philippines.
Keywords: Indigenous peoples -- Philippines -- Research; Research -- Methodology